2012
DOI: 10.5114/aoms.2012.29526
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima-media thickness and arterial stiffness in type 1 diabetic patients with and without microangiopathy

Abstract: A b s t r a c tIntroduction: The aim of the study was to assess carotid intima-media thickness (CIMT) as a subclinical marker of atherosclerosis and arterial stiffness in type 1 diabetic patients in relation to microangiopathy. Material and methods: We included 87 type 1 diabetic patients (44 women, 43 men), median age 34 years (interquartile range [IQR] 29-43), median disease duration 10 years (IQR: 9-14), mean ± standard deviation (SD) glycated haemoglobin (HbA 1c ) 8.4 ±1.4%. Fifty patients had at least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…This hypothesis is consistent with several studies that showed a relation between reduced compliance in large arteries and pathological conditions that are related with flow disturbances in the microcirculation. [31][32][33][34] In a cross-sectional population study, increased brachial-ankle PWV affected the microcirculation in brains and kidneys in a way leading to cerebral asymptomatic lacunar infarction 33 and renal albuminuria, 34 respectively. In another population study that included 443 healthy subjects, PWV was significantly associated with silent cerebral microbleeds on brain MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is consistent with several studies that showed a relation between reduced compliance in large arteries and pathological conditions that are related with flow disturbances in the microcirculation. [31][32][33][34] In a cross-sectional population study, increased brachial-ankle PWV affected the microcirculation in brains and kidneys in a way leading to cerebral asymptomatic lacunar infarction 33 and renal albuminuria, 34 respectively. In another population study that included 443 healthy subjects, PWV was significantly associated with silent cerebral microbleeds on brain MRI.…”
Section: Discussionmentioning
confidence: 99%
“…31 Also, one study reported a relation between arterial stiffness and microangiopathy in a diabetes mellitus type 1 population. 32 On a local level, another aspect that needs to be considered is the fluid dynamics, which can underlie the connection between arterial stiffness and atherosclerotic plaque. Although flow in the common carotid artery has a laminar profile, this can evolve to velocity profile skewing at the carotid bifurcation, leading to regions in which the wall shear stress is low.…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance of the test material was measured at wavelengths of 450 and 540 nm. The concentrations of the different parameters were determined from a standard curve …”
Section: Methodsmentioning
confidence: 99%
“…Predictors of the occurrence of diabetic microangiopathy have been identified, showing that beyond the duration of diabetes, systolic and diastolic blood pressure, postprandial glucose, HbA 1c levels also elevated serum TG and LDL cholesterol levels were responsible for the increased risk of angiopathy [14].…”
Section: Influence Of Lipids Profle On Complications Of Type 1 Diabetesmentioning
confidence: 99%